The interaction of APEX1 variant with polycyclic aromatic hydrocarbons on increasing chromosome damage and lung cancer risk among male Chinese. Issue 1 (22nd August 2014) - Li, Xiaoliang; Wei, Jinyu; Xu, Ping; Yin, Xiangqian; Hu, Die; Zhang, Xiao; Liu, Li; Zhang, Kai; Zhou, Changchun; Wang, Tian; Zhang, Xiaomin; He, Meian; et al.
<x xml:space="preserve">Abstract</x> Polycyclic aromatic hydrocarbons (PAHs) are the most significant contributors to tobacco‐induced lung carcinogenesis. Apurinic/apyrimidinic endonuclease 1 (APE1) is a central enzyme in the removal of apurinic/apyrimidinic sites caused by DNA damaging agents. This study aimed to investigate the potential interaction of APEX1 polymorphisms and PAHs on genetic damage and lung cancer risk among male Chinese. We recruited an occupational cohort of 922 male coke oven workers and determined their DNA damage levels by calculating the lymphocytic micronucleus (MN) frequencies. Two well‐studied APEX1 polymorphisms (−307A > C and Asp148Glu) and their associations with MN frequencies were examined. The impact of MN‐related single nucleotide polymorphism (SNP) on lung cancer risk was further investigated in two case‐control studies including 1634 male lung cancer patients and 1678 controls. It was shown that, the APEX1 148Glu allele was associated with significantly higher MN frequencies than 148Asp allele, with strongest associations among the highest PAH‐exposure workers (P = 0.008). The APEX1 148Glu allele was also associated with increased lung cancer risk among male smokers, especially among heavy smokers in both case‐control studies (odd ratio: 4.40, 95%CI: 3.29–5.72). In addition, APEX1 148Glu variant interacts with smoking in increasing male lung cancer risk, as measured by the attributable proportion due to interaction, which was 0.23 (95%CI: 0.06–0.39). This study showed evidence on interaction between APEX1 148Glu variant and cigarette smoking in increasing lung cancer susceptibility among male Chinese, which may be due to the synergistic effects of APEX1 148Glu and PAHs in increasing chromosome damage levels. The results provide a new insight into gene‐interactions in lung carcinogenesis. © 2014 Wiley Periodicals, Inc.